Prostate focal therapy: the rule or exception?. Issue 6 (November 2018) - Tay, Kae Jack
Abstract : Purpose of review: Prostate focal therapy has the potential to preserve urinary and sexual function while eliminating clinically significant cancer in a subset of men with low-volume, organ-confined prostate cancer. This systematic review aims to examine current evidence to determine the efficacy and safety of focal therapy for standard clinical application. Recent findings: Focal therapy reduces the rate of cancer progression and conversion to radical therapy in men on active surveillance for prostate cancer. As a strategy, success in focal therapy is heavily dependent on the use of imaging and targeted biopsies. Despite advances in these areas, there remains a small but significant risk of under-detecting clinically significant cancer. Similarly, under-estimation of tumor volume may contribute to infield recurrences and close attention must be paid to the ablation margin. Although long-term oncological outcomes remain lacking, focal therapy has a low complication rate, minimal impact on urinary continence and a moderate impact on erectile function. Summary: With the appropriate expertise in imaging, targeted biopsy and targeted ablation, focal therapy is a good option in men with low–intermediate risk cancer who are willing to maximize their urinary and sexual function. However, close posttreatment surveillance and the possibility of conversion to whole gland therapy must be accepted.